New tool to control and monitor weighted vest training load for sprinting and jumping in soccer - Carlos-Vivas, J.; Freitas, T. T.; Cuesta, M.; Perez-Gomez, J.; De Hoyo, M.; Alcaraz, E. P. (The Journal of Strength and Conditioning Research, 2019)
The purpose of this study was to develop 2 regression equations that accurately describe the relationship between weighted vest loads and performance indicators in sprinting (i.e., maximum velocity, Vmax) and jumping (i.e., maximum height, Hmax). Also, this study aimed to investigate the effects of increasing the load on spatio-temporal variables and power development in soccer players and to determine the "optimal load" for sprinting and jumping. Twenty-five semiprofessional soccer players performed the sprint test, whereas a total of 46 completed the vertical jump test. Two different regression equations were developed for calculating the load for each exercise. The following equations were obtained: % body mass (BM) = -2.0762·%Vmax + 207.99 for the sprint and % BM = -0.7156·%Hmax + 71.588 for the vertical jump. For both sprinting and jumping, when the load increased, Vmax and Hmax decreased. The "optimal load" for resisted training using weighted vest was unclear for sprinting and close to BM for vertical jump. This study presents a new tool to individualize the training load for resisted sprinting and jumping using weighted vest in soccer players and to develop the whole force-velocity spectrum according to the objectives of the different periods of the season.